Genetic analysis of new genes for resistance to brown planthopper in rice mutants - , Mugiono (Zuriat, 1992)
Rice breeding using induced mutation has succesfully produced several mutant lines resistant to brown planthopper. In order to beable to utilize these mutant lines further in a breeding programme it is essential to study the inheritance of resistance to brown planthopper in rice mutants MG-8 and MG-18 was studied in the Center For Application of Isotope and Radiation. Pasar Jumat. The result showed that the resistance of MG-8 and MG-18 to brown plathopper was controlled by a single recessive gene and this gene is not allelic to bph-2 of the ASD-7 genotype.